Safety method, Spectrophotometric Determination of Sulfamethaxazole drug in bulk and Pharmaceutical Preparations (Baghdad Science Journal, 2025)
A simple, cheap, fast, accurate, Safety and sensitive spectrophotometric method for the determination of sulfamethaxazole (SFMx), in pure form and pharmaceutical dosage forms. has been described The Method is based on the diazotization of the drug by sodium nitrite in acidic medium at 5Cº followed by coupling with salbutamol sulphate (SBS) drug to form orange color the product was stabilized and measured at 452 nm Beer’s law is obeyed in the concentration range of 2.5-87.5 ?g ml-1 with molar absorptivity of 2.5x104 L mole-1 cm-1. All variables including the reagent concentration, reaction time, color stability period, and sulfamethaxazole /salbutamol ratio were studied in order to optimize the reaction conditions. No interferences were observed Results of analysis were validated statistically and by recovery studies. These methods are successfully employed for the determination of sulfamethaxazole in some pharmaceutical preparations.. The developed method is easy to use and accurate for routine studies relative to HPLC and other techniques.